ETIKA SAMIN - Mikka Wildha Nurrochsyam (Jantra., 2019)
Samin people are farmers who practice the teachings of Samin Surosentiko (1857-1914). This research about Samin ethics has two objectives. Firstly, to formulate the ethical standards of the Samin community as an agrarian society. Secondly, using Lawrence Kohlberg’s theory of the development of moral consciousness this research want to reveal the level of moral consciousness of the Samin community. This qualitative research obtained the data from in-depth interviews with informants that consist of Samin figures from Blora, Pati, and Bojonegoro. The data were analysed using theoretical construction methods. The result has indicated that there are three Samin ethical principles, namely honesty, harmony, and brotherhood. These three principles of Samin’s ethics can be categorized as still in the conventional level, seen in the structure of moral consciousness of Kohlberg. The moral consideration of Samin people tend to be based on the expectations of their group.